Degradação das margens do córrego jenipapo na região do povoado farturão municipio de babaçulandia-to. - SANTOS, Joanilson Pereira (Universidade Federal do Tocantins, 2023)
The objective was to conduct a study about the degradation of the banks of the Jenipapo stream in the region of Povoado Farturão in the municipality of Babaçulândia. To verify the environmental legislation in force related to the degradation of streams. To analyze the main damage caused by the degradation of the banks of the Jenipapo stream and the effects of the occupation by the community of the Farturão Village. In addition to conducting a literature review on the degradation of stream banks, the concept and importance of preserving riparian forests and gallery forests, anthropic action and occupation of riparian forest areas. Among the main impacts observed in the stream Jenipapo, the removal of riparian forest stands out, as it is one of the main influences of degradation, contributing to the emergence and intensity of erosive processes, among other problems that culminate in the impoverishment of the soil, silting up of waterways and a lack of control of biodiversity. From the analysis of the results, it was possible to verify that in conjunction with the urbanization process, the riparian forests also suffer anthropic pressure for several factors: they are preferential locations for the opening of roads,for the implantation of agricultural and pasture crops; for cattle ranchers, they represent obstacles for the cattle to access the watercourse.